Spontaneous Rupture of Uterine Artery in a 14-Week Pregnant Woman - João Paulo Mancusi de Carvalho; Luciano Augusto de Carvalho Severo; Maria Helena Mancusi de Carvalho; Marina de Paula Andres; Mariano Tamura Vieira Gomes; Sergio Podgaec (Hindawi Limited, 2016)
We report a case of uterine artery rupture in a woman at 14 weeks' gestation who presented with abdominal pain, tachycardia, and hypotension and underwent a diagnostic laparoscopy. During this procedure, a spontaneous rupture of the left uterine artery was diagnosed and the surgery was converted into a laparotomy. The artery was bound to its origin and to its distal uterine portion. The patient exhibited excellent postoperative recovery and was discharged two days after the surgery. The pregnancy continued without other maternal or fetal complications, and the patient delivered a healthy newborn via cesarean section at 39 weeks of gestation.